Time- and Ventricular-Specific Expression Profiles of Genes Encoding Z-Disk Proteins in Pressure Overload Model of Left Ventricular Hypertrophy - Knyazeva, Anastasia; Krutikov, Alexander; Golovkin, Alexey; Mishanin, Alexander; Pavlov, Georgii; Smolina, Natalia; Hushkina, Anastasia; Sejersen, Thomas; Sjoberg, Gunnar; Galagudza, Mikhail; Kostareva, Anna (Frontiers in Genetics, 2019)
Mechanotransduction is an essential mechanism of transforming external mechanical stimulis to biochemical response. In cardiomyocytes mechanotransduction plays an important role in contraction, stretch sensing and homeostasis regulation. One of the major mechanosensitive area in cardiomyocytes, the Z-disk, consists of numbers of structural and signaling proteins, that may undergo conformational or gene expression changes under pathological stress conditions. In present study we examined a rat model of pressure overload cardiac hypertrophy validated by echocardiographic and histopathological examinations. We revealed, that during hypertrophy progression expression of several genes encoding Z-disk proteins (Actn2, Ldb3, Cmya5, Nebl) is different at early and late points of cardiac remodeling. Moreover, expression patterns of several genes are opposite in myocardium of overloaded left ventricle and hemodynamically unaffected right ventricle, and expression profiles in interventricular septum are more similar to right ventricle. Additionally, we revealed inconsistencies between mRNA and protein level changes of Actn, one of the major structural Z-disk element. All these findings point out, that investigated Z-disk proteins participate in pathological stress adaptation through undergoing the gene expression changes, and suggest the novel important role of hypertrophic response modulation during different stages of cardiac remodeling.